Response of broiler to supplementation of potassium chloride during summer (Asian Journal of Medical and Biological Research, 2015)
A total of 90 day old as hatched Cobb 500 broilers had free access to a pre-starter diet (crumble) from day old to 14 days of age. A starter diet (pellet) was provided up to end of the experiment. Broilers were allocated to 0 (control), 0.2 or 0.4% of potassium chloride (KCl) in drinking water and reared up to 500, 1000 or 1500g target weights to vary the rearing period. The study was aimed at to assess broiler performance (growth and meat yield) altered by KCl supplementation in drinking water in a hot and humid summer. KCl had no effect (p>0.05) on growth and meat yield characteristics of broilers except feed conversion (p0.05) with target weights. However, 0.4% KCl level slightly improved feed intake, growth rate and performance index. Increasing level of KCl tended to increase most of the major meat yield characteristics. On the basis of results of this study, it may be concluded that, supplementation of KCl in drinking water in summer improved the feed conversion of broilers. However, further experiments using several doses of KCl may be conducted to confirm the appropriate doses of supplementation.Asian J. Med. Biol. Res. June 2015, 1(1): 103-108